2016
DOI: 10.1111/ejn.13191
|View full text |Cite
|
Sign up to set email alerts
|

Microglia‐derived purines modulate mossy fibre synaptic transmission and plasticity through P2X4 and A1 receptors

Abstract: Recent data have provided evidence that microglia, the brain-resident macrophage-like cells, modulate neuronal activity in both physiological and pathophysiological conditions, and microglia are therefore now recognized as synaptic partners. Among different neuromodulators, purines, which are produced and released by microglia, have emerged as promising candidates to mediate interactions between microglia and synapses. The cellular effects of purines are mediated through a large family of receptors for adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 71 publications
4
23
0
1
Order By: Relevance
“…ATP can also be released through multiple other pathways (Hamann and Attwell 1996;Lazarowski 2012;Orellana et al 2013;Oya et al 2013;Zhang et al 2007a;reviewed in Bodin and Burnstock 2001) from different cell types, namely terminals, dendrites, and axons from neurons (White 1978;Pankratov et al 2006Pankratov et al , 2007Zhang et al 2007b;Fields 2011a,b;Lovatt et al 2012), astrocytes (Newman 2003;Halassa et al 2009;Koizumi 2010) and microglia (Dou et al 2012;Imura et al 2013;George et al 2015). This is in accordance with the multiple physiological roles that have been ascribed to extracellular ATP (reviewed in Rodrigues et al 2015): (i) ATP can act as a neurotransmitter, as heralded by the P2X receptor-mediated ATPergic transmission described in brain circuits (Edwards et al 1992;Bardoni et al 1997;Nieber et al 1997;Pankratov et al 1999Pankratov et al , 2002Mori et al 2001); (ii) ATP is also a controller of inflammation (reviewed in Di et al 2009;Idzko et al 2014), with multiple actions on microglia (reviewed in Koizumi et al 2013) impacting on the function of astrocytes and neuronal networks (Pascual et al 2012;George et al 2016); (iii) ATP and adenosine both regulate oligodendrocyte differentiation and myelination (Agresti et al 2005) in an activity-dependent manner (Fields 2006); (iv) ATP is a paracrine modulator of astrocytes and a neuron-or microglia-to-astrocyte signal by sustaining Ca 2+ -waves, the main mechanism to propagate glial excitability and intercellular communication (Guthrie et al 1999;...…”
Section: Dynamics Of Extracellular Adenosine Generationsupporting
confidence: 52%
See 2 more Smart Citations
“…ATP can also be released through multiple other pathways (Hamann and Attwell 1996;Lazarowski 2012;Orellana et al 2013;Oya et al 2013;Zhang et al 2007a;reviewed in Bodin and Burnstock 2001) from different cell types, namely terminals, dendrites, and axons from neurons (White 1978;Pankratov et al 2006Pankratov et al , 2007Zhang et al 2007b;Fields 2011a,b;Lovatt et al 2012), astrocytes (Newman 2003;Halassa et al 2009;Koizumi 2010) and microglia (Dou et al 2012;Imura et al 2013;George et al 2015). This is in accordance with the multiple physiological roles that have been ascribed to extracellular ATP (reviewed in Rodrigues et al 2015): (i) ATP can act as a neurotransmitter, as heralded by the P2X receptor-mediated ATPergic transmission described in brain circuits (Edwards et al 1992;Bardoni et al 1997;Nieber et al 1997;Pankratov et al 1999Pankratov et al , 2002Mori et al 2001); (ii) ATP is also a controller of inflammation (reviewed in Di et al 2009;Idzko et al 2014), with multiple actions on microglia (reviewed in Koizumi et al 2013) impacting on the function of astrocytes and neuronal networks (Pascual et al 2012;George et al 2016); (iii) ATP and adenosine both regulate oligodendrocyte differentiation and myelination (Agresti et al 2005) in an activity-dependent manner (Fields 2006); (iv) ATP is a paracrine modulator of astrocytes and a neuron-or microglia-to-astrocyte signal by sustaining Ca 2+ -waves, the main mechanism to propagate glial excitability and intercellular communication (Guthrie et al 1999;...…”
Section: Dynamics Of Extracellular Adenosine Generationsupporting
confidence: 52%
“…; George et al . ); (iii) ATP and adenosine both regulate oligodendrocyte differentiation and myelination (Agresti et al . ) in an activity‐dependent manner (Fields ); (iv) ATP is a paracrine modulator of astrocytes and a neuron‐ or microglia‐to‐astrocyte signal by sustaining Ca 2+ ‐waves, the main mechanism to propagate glial excitability and intercellular communication (Guthrie et al .…”
Section: The Adenosine Modulation System – Dynamics Of Its Extracellumentioning
confidence: 99%
See 1 more Smart Citation
“…also recently showed that CD39 −/− microglia had attenuated ramification, a phenotype that has been correlated with microglia quiescence. Interestingly, microglia‐derived ATP and adenosine mediate synaptic plasticity and transmission and microglia‐dependent modulation of neuronal activity has been shown to depend on neuronal hemi‐channels, channels important for ATP release. Therefore, our findings do not rule out the possibility that CD39 −/− mice may have altered neuron–microglia communication that could contribute to the observed seizure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In oligodendrocytes, A 1 Rs promote myelination during axonal maturation (Stevens et al, ), and contribute to white matter loss in pathology (Kim et al, ). In microglia, A 1 R activation on microglia can regulate proliferation (Haselkorn et al, ), limit the inflammatory response (Tsutsui et al, ), contribute to the neuroprotective effects associated with adenosine delivery (Lauro et al, ; Pedata et al, ), and modulate short‐term synaptic transmission and plasticity (George et al, ). Many other functions are mediated by purinergic signaling through other receptors and pathways, as well.…”
Section: Discussionmentioning
confidence: 99%